IMPROVING STUDENTS"™ SKILL IN WRITING NEWS ITEM TEXT BY IMPLEMENTING SILLY NEWS REPORTS GAME - Abdullah, Anjas; Aprialiaswati, Rahayu (Journal of English Education Program, 2022)
The tendency to ignore the lesson and make distraction in writing course led to bad result in writing assessment especially in news item text. This research intended to see how silly news reports game improve students"™ skill in writing news item text particularly in improving students"™ motivation as interest in writing. This research was a Classroom Action Research (CAR) in three cycles to 37 students at class XII IPA 6 of SMAN 3 Pontianak in academic year 2019/2020. The result of the data collection showed that implementing silly news reports game improved students"™ skill in writing news item text in terms of writing composition and grammar accuracy on using reported speech, and improved students"™ motivation as interest in writing. Based on the observation, the highlight of the improvement by the game implementation was on the content of silly news reports game which is ridiculous yet easy to understand supported by the guided question worksheets that made the students able to produce a well-organized writing by considering the composition of the writing such as the organization of the text and the language features used in the news item text. The improvement of each cycle differed one to another. While cycle one found the gap of the student improvement, cycle two solved the problem of students writing composition and using reported speech, and cycle three solved the problem of students"™ behaviour. Therefore, the researcher recommends that the teacher implement silly news reports game to teach news item text of writing course.